(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
New data on the distribution of some Chrysomelidae Clytrinae from Near and Middle East are given. The following species or subspecies, are recorded for the first time from the countries here reported: Labidostomis basanica J. Sahlberg for Turkey, Jordan and Iraq; L. brevipennis Faldermann for Iraq; L. longimana (Linnaeus) for Armenia; L. hebraea (Lacordaire) for Turkey; L. medvedevi Warchalowski for Armenia; L. nuristanica subsp. afghanica L. Medvedev for Pakistan; Clytra laeviuscula Ratzeburg for Armenia; Paraclytra crocata (Lacordaire) for Oman; Tituboea arabica (G. A. Olivier) for Iraq; T. macropus (Illiger) for Lebanon; T. ornaticollis L. Medvedev for Iraq; T. tredecimpunctata (Desbrochers des Loges) for Jordan; T. puncticollis (L. Medvedev) for Pakistan; Smaragdina djebellina (Lefevre) for Jordan; S. scutellaris (Lefevre) for Jordan; Cheilotoma erythrostoma Faldermann for Turkey and Iran.